Zuhd dan Mahabbah dalam Ekonomi Islam Kontemporer: Perspektif Tasawuf sebagai Solusi Krisis Nilai Bisnis - Bayu Fermadi; Moh. Hasan Fauzi; Moch. Bashori Alwi; Yuni Pangestutiani (Journal of Innovative and Creativity, 2024)
The contemporary economic and business landscape is experiencing a profound value crisis marked by the dominance of materialism, consumerism, and instrumental rationality. These tendencies have contributed to ethical problems such as social inequality, declining integrity, and the erosion of public trust, revealing the limitations of mainstream economic paradigms in addressing the moral and spiritual dimensions of human life. This study aims to examine the role of Sufi values, particularly zuhd and mahabbah, as an alternative ethical framework within contemporary Islamic economics. Employing a qualitative approach, this research conducts a systematic literature review using descriptive and thematic analysis of relevant scholarly publications published between two thousand seventeen and two thousand twenty five. The findings indicate that zuhd and mahabbah offer a holistic and transformative ethical framework for economic activity. Zuhd functions as an internal mechanism for restraining excessive material attachment, thereby reducing consumerism, preventing economic crimes, and promoting sustainability. Meanwhile, mahabbah fosters a relational ethic grounded in divine love that strengthens trust, social solidarity, and integrity at both individual and institutional levels. The study further demonstrates that Sufi values are relevant and applicable across various contexts, including education, business organizations, and community based economic initiatives. Overall, the Sufi approach has the potential to complement mainstream economic paradigms by reinforcing ethical and spiritual dimensions, thereby contributing to the development of a more just, humane, and sustainable model of Islamic economics.